2013
DOI: 10.1007/s00586-013-2810-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pilot hole on biomechanical and in vivo pedicle screw–bone interface

Abstract: Purpose To experimentally study the influence of pilot hole diameter (smaller than or equal to the internal (core) diameter of the screw) on biomechanical (insertion torque and pullout strength) and histomorphometric parameters of screw-bone interface in the acute phase and 8 weeks after pedicle screw insertion. Methods Fifteen sheep were operated upon and pedicle screws inserted in the L1-L3 pedicles bilaterally. The pilot hole was smaller (2.0 mm) than the internal diameter (core) of the screw on the left si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
(60 reference statements)
2
26
0
Order By: Relevance
“…Multiple studies have been conducted to examine stability characteristics of pedicle screw systems using polyurethane foams, 4,5,13 animal spines, 16,23 and human cadaveric spines. Although polyurethane foams have mechanical properties simulating human cancellous bone and offer the advantages of homogeneity and reproducibility, it is difficult to replicate the complex and 3D structure of the pediclevertebral body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have been conducted to examine stability characteristics of pedicle screw systems using polyurethane foams, 4,5,13 animal spines, 16,23 and human cadaveric spines. Although polyurethane foams have mechanical properties simulating human cancellous bone and offer the advantages of homogeneity and reproducibility, it is difficult to replicate the complex and 3D structure of the pediclevertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…19 These factors play important roles in pedicle screw fixation and may be topics of further consideration. 5,23 A second limitation is that we used FE models of single segments of the vertebra. The multiple segment and screw-rod construct model provides a better representation of the actual situation.…”
mentioning
confidence: 99%
“…16 Should a pilot hole be used, and should it be smaller than the internal screw diameter, there is a possibility of an increase in radial displacement and blockage (impaction) of cancellous bone while the screw (especially the core) is driven into the bone itself. This, in turn, involves more interaction between the screw and the adjacent bone and more bone makes its way into the thread.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19 In the present study, the comparative analysis of the pullout strength of self-drilling and self-tapping screws revealed higher strength in the former, which is due to the higher degree of interaction between the bone and thread (or, in the present study, the greater quantity of polyurethane foam in the thread). 16 In clinical applications, self-drilling screws should be used carefully, especially in 1.5 mm diameter systems, due to the possibility of screw head damage.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for enhancing screw fixation is modification of the screw path before screw insertion, including the pilot and tapping holes. Biomechanical studies demonstrated that a pilot hole size smaller than the core diameter of the screw and an under-size-tapping smaller than the outer diameter of the planned screw improve the fixation strength of pedicle screws 3,4) . Another strategy influencing screw fixation is alteration of the transpedicular screw path from the conventional screw path.…”
Section: Introductionmentioning
confidence: 99%